2020
DOI: 10.3906/sag-1912-196
|View full text |Cite
|
Sign up to set email alerts
|

Surface enhanced Raman spectroscopy as a novel tool for rapid quantification of heroin and metabolites in saliva

Abstract: Background: Heroin can be detected and quantified by certain analytical methods, however, forensic professionals and criminal laboratories study for cheaper and faster detection tools. Surface-enhanced Raman spectroscopy (SERS) rises as a possible alternative tool with its widening application spectra. There are few studies regarding Raman and SERS spectra of heroin and its metabolites, which are unfortunately controversial. In this study, we compared five different surfaces in order to find out more efficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…And provides a well direction for the future application of AD disease. This indicates that Raman spectroscopy has a good application in the diagnosis of diseases, which is not only fast and efficient ( 31 ), but also widely used ( 32 ). It is also a non-invasive diagnostic tool ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…And provides a well direction for the future application of AD disease. This indicates that Raman spectroscopy has a good application in the diagnosis of diseases, which is not only fast and efficient ( 31 ), but also widely used ( 32 ). It is also a non-invasive diagnostic tool ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Akçan et al also explored heroin and its metabolites but in saliva rather than urine in 2020 with a 785 nm microscope Raman instrument (Akçan et al, 2020). Various SERS substrates were explored to determine the best surface for analysis including silver nanorods, silver nanosurfaces, gold nanoparticle/nanocellulose surfaces, gold nanoparticle/ polyaniline surfaces, TLC silica gel aluminum sheets, and gold nanorod arrays.…”
Section: Fentanyl and Opioidsmentioning
confidence: 99%
“…[69] 6-MAM has also been reported on gold colloids and gold nanorod arrays. [21,33] Because we used a 10-ppm heroin solution for the pH study, it is not surprising that the 6-MAM degradation product formed in this pH 11 solution over time was not strongly observed in the SERS measurement on the gold sol-gel. However, the weak feature observed at around 627 cm À1 in the SERS of the pH 11 solution (Figure 13) measured after equilibrating for over an hour, although not conclusive, would appear to support its formation corresponding to the disappearance of heroin due to hydrolysis/ deacetylation.…”
Section: Effects Of Ph On Drug Measurements With the Sers-active Subs...mentioning
confidence: 99%
“…SERS is versatile in its use and application and offers the ability to detect various drugs of concern at low concentration levels directly from surfaces, [ 9 ] as trace components in tablets or powders, [ 10 ] in wastewater, [ 11 ] and in biofluids, [ 12–26 ] including saliva. [ 27–34 ] Additional studies have reported the SERS detection of a wide range of abused drugs in solution, [ 35 ] such as cocaine, [ 36 ] amphetamines, [ 37,38 ] ring substituted amphetamines, [ 39–41 ] bath salts, [ 42,43 ] opioids [ 21,35,44–48 ] including drug mixtures laced with fentanyl, [ 49–53 ] hallucinogens, [ 27,54,55 ] marijuana active ingredients, [ 35 ] and other prescription and over the counter drugs. [ 35 ] Sensitivity at low detection limits is possible even at sub‐nanogram per milliliter levels, as has been observed for fentanyl in wastewater [ 11 ] and reported in aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation